Hubungan Intensitas Kebisingan dan Karakteristik Individu dengan Gangguan Pendengaran pada Pekerja Wilayah Operasi PT X - Faa’izah Arsyi Osci Hm; Ida Umarul Mufidah; Nico Linggi Pongmasangka (POLITEKNIK KETENAGAKERJAAN, 2025)
Hearing examination in the PT X operation area shows the results of 2 workers experiencing mild deafness, 1 worker experiencing moderate deafness, and 2 workers experiencing severe deafness. Measurement of work environment noise in the PT X operation area at 21 out of 23 points has results exceeding the threshold value in accordance with the Minister of Manpower Regulation Number 5 of 2018. This study aims to analyze the relationship between noise intensity and individual characteristics with hearing loss in workers at PT X. This study used a quantitative method with a cross sectional design. Data were collected from 32 workers who had conducted audiometric examinations, as well as noise intensity measurements at 23 points of PT X's marine operations area. Data analysis was performed using the Spearman correlation test. The results showed that there was no significant relationship between noise intensity and hearing loss (significance value 0.376 > p (0.05)). However, there is a significant relationship between age and hearing loss (significance value 0.014 < p (0.05); r = 0.429. While noise intensity, tenure, length of employment, and use of hearing protection device (HPD) did not show a significant relationship with hearing loss. It is recommended to implement the